Upaya Meningkatkan Perilaku Altruistic Melalui Layanan Bimbingan Kelompok Teknik Sosiodrama Di SMP Swasta Nur Azizi Tanjung Morawa - Hasibuan Jhohan Moro; Nur Asyah (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU, 2024)
This study aims to improve altruistic behavior through sociodrama-based group guidance services at Nur Azizi Private Middle School, Tanjung Morawa. This study will involve approximately eight students with low altruistic behavior and then provide them with sociodrama-based group guidance services. The research sample was selected based on students with the lowest altruistic behavior scores. Data collection for this study was conducted using observation sheets as an instrument. Data analysis used a percentage formula by accumulating the data in groups. The results of the study indicate several conclusions, namely: (1) This study found that sociodrama-based group guidance services can improve altruistic behavior in students at Nur Azizi Private Middle School, Tanjung Morawa; (2) There was a change in students' altruistic behavior after implementing sociodrama-based group guidance services, with a percentage of 25% in cycle 1 and 87.5% in cycle 2.